NATIONAL SOCIAL INVESTMENT PROGRAMME (N-SIP), VULNERABLE POPULATIONS AND SUSTAINABLE DEVELOPMENT GOALS (SDGS) IN ENUGU STATE, NIGERIA: TRACING A NEXUS - ONAH, F. N; ANIKWE, S. O.; ONAH, FAB O. (International Journal of Psychosocial Rehabilitation, 2021)
The National Social Investment Programme (N-SIP) of Nigeria is a social welfare initiative createdby the Federal Government in 2015 to ensure equitable distribution of resources to vulnerablepopulations to address, hunger, poverty and well-being which incidentally are the first threeSustainable Development Goals. In spite of the huge N-SIP annual budget, the well-being ofvulnerable populations has not shown any satisfactory improvement. The main goal of this study wasto trace the impact of N-SIP on SDGs 1, 2 and 3 in Enugu State, Nigeria. The specific objectives areto; (a) find out the impact of Conditional Cash Transfer of N-SIP on poverty and well-being ofvulnerable populations in Enugu State; (b) examine the effectiveness of the home-grown schoolfeeding programme in Enugu State and (c) find out the obstacles impeding the success of N-SIP. Thestudy used a multi-dimensional approach which includes visits to a sample of the 421 Communitiesin Enugu State, documentary evidence, interviews with key informants (KIs) in relevant ministriesand Focus Group Discussions. The findings were analyzed and discussed based on sustainabledevelopment theory which is the study’s theoretical platform. The less than satisfactory impact of NSIP on poverty and hunger of vulnerable populations in Enugu State was demonstrated. The paperargues that N-SIP lacked focus, predicated on imaginary data and unsustainable. We ended thepaper by packaging some proactive policy intervention measures including putting more efforts indata banking and management.